Distribution des revenus et développement : quelques faits stylisés - Ahluwalia, Montek (L'Actualité économique)

(untitled) (HEC Montréal, 1977)
AbstractIn recent years, the relationship between income distribution and the process of development has come under increasing scrutinity. Much of the debate has focused on the hypothesis, originally advanced by Simon Kuznets, that the secular behavior of inequality follows an inverted U shaped pattern which inequality first increasing and then decreasing with development. This hypothesis has become so much a part of the conventional wisdom on this subject that it has generated considerable skepticism about the welfare implications of the development process. Indeed, on some interpretations, developing countries face the grim prospect not just of increasing relative inequality, but also of declining absolute incomes for the lower income groups.The object of the article is to re-examine the empirical basis for this hypothesis using a recent compilation of cross-country data made at the World Bank. The author uses multiple regression to estimate cross country relationships between inequality, as reflected in the income shares of various percentile groups, and selected explanatory variables reflecting different aspects of the development process. The results suggest that while there may be a secular time path for inequality which developing countries must traverse and which contains a phase of increasing inequality, there is at least no evidence that faster growing countries show higher inequality at the same level of development than slower growing countries.